Meminimalisir Kerugian Usaha Menggunakan Metode Economic Order Quantity (EOQ) Berbasis Data Base Pelanggan - Ulfah, Baiq Rizka Milania; Halpiah, Halpiah; Arianti, Nabila Finda; Ayu, Lisna; Adwiyah, Rabiatul; Putra, Hery Astika; Aryandani, Aisyah; Arfin, Ahmad (Jurnal Pengabdian UNDIKMA, 2025)
This community service activity aims to minimize business losses by applying the Economic Order Quantity (EOQ) method, which optimizes inventory ordering to reduce costs based on customer database analysis. The implementation of this program employed the Participatory Rural Appraisal (PRA) approach, consisting of several stages: pre-implementation, education, mentoring, training, and evaluation. The results show a significant reduction in business losses from 40% to 10%. In addition, sales increased from 30% to 60%, and customer growth rose from 33% to 67%. The impact of this program indicates that the partner is now able to reduce business losses, increase sales, expand the customer base, and develop two new banana-based product variants—pisang molen and pisang sale—which contribute to higher business profits.